Grit to great how perseverance, passion, and pluck take you from ordinary to extraordinary - Kaplan Thaler, Linda; Koval, Robin (Crown Business, 2015)
"In Grit to Great, Linda Kaplan Thaler and Robin Koval tackle a topic that is close to their hearts, one that they feel is the real secret to their own success in their careers--and in the careers of so many people they know and have met. And that is the incredible power of grit, perseverance, perspiration, determination, and sheer stick-to-it-tiveness. We are all dazzled by the notion that there are some people who get ahead, who reach the corner office because they are simply gifted, or well-connected, or both. But research shows that we far overvalue talent and intellectual ability in our culture. The fact is, so many people get ahead--even the gifted ones--because they worked incredibly hard, put in the thousands of hours of practice and extra sweat equity, and made their own luck. And Linda and Robin should know--they are two girls from the Bronx who had no special advantages or privileges and rose up through their own hard work and relentless drive to succeed to the top of their highly competitive profession. In a book illustrated with a cornucopia of stories and the latest research on success, the authors reveal the strategies that helped them, and countless others, succeed at the highest levels in their careers and professions, and in their personal lives. They talk about the guts--the courage--necessary to take on tough challenges and not give up at the first sign of difficulty. They discuss the essential quality of resiliency. Everyone suffers setbacks in their careers and in life. The key, however, is to pick yourself up and bounce back. Drawing on the latest research in positive psychology, they discuss why optimists do better in school, work, and on the playing field--and how to reset that optimistic set point. They talk about industriousness, the notion that Malcolm Gladwell popularized with the 10,000-hour rule in his book Outliers. Creativity theorist Mihaly Csikszentmihalyi believes it takes a minimum of 10 years for one's true creative potential to be realized. And the authors explore the concept of tenacity--the quality that allows us to remain focused and avoid distraction in order to get the job done--an increasingly difficult task in today's fragmented, cluttered, high-tech, connected world. Written in the same short, concise format as The Power of Nice and leavened with the natural humor that characterizes Linda's and Robin's lives--and books--Grit to Great is destined to be the book everyone in business needs"--